2014
DOI: 10.1177/1528083714534708
|View full text |Cite
|
Sign up to set email alerts
|

Barium sulfate/regenerated cellulose composite fiber with X-ray radiation resistance

Abstract: In this article, submicron barium sulfate particles, as the radiation-resistant component, were incorporated into regenerated cellulose spinning solution. Then a series of X-ray radiation-resistant fibers were fabricated via a primarily industrialized wet-spinning trail, and the resultant fibers were knitted into fabrics by knitting loom. The morphology and structure of the fibers were studied with the aid of scanning electron micrography, Fourier-transform infrared spectroscopy, and X-ray diffraction. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…A higher magnification image (Figure 2b) reveals that each fiber has a ridge surface with grooves parallel to the fiber axis direction. This shape is typical of wet spun viscose fibers [35] used as precursor material in the activated carbon fabric manufacture. At an electropolymerization time of 10 min, PAni can already be discerned on the surface of ACC (Figure 2c–d).…”
Section: Resultsmentioning
confidence: 97%
“…A higher magnification image (Figure 2b) reveals that each fiber has a ridge surface with grooves parallel to the fiber axis direction. This shape is typical of wet spun viscose fibers [35] used as precursor material in the activated carbon fabric manufacture. At an electropolymerization time of 10 min, PAni can already be discerned on the surface of ACC (Figure 2c–d).…”
Section: Resultsmentioning
confidence: 97%
“…All images exhibit a rough surface with a granular topography that is typical of viscose rayon morphology [ 31 ]. Filaments presented a wrinkled surface owing to the coagulation of the material [ 35 ]. In both cases, we can see that the cross section presents cavities formed generally by the solidification of the viscose [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cross section of the fibers presents a lobed or circular serrated (jagged) shape with a highly rough/striated surface; this is characteristic of the coagulation process of viscose rayon fibers because this is found first on the surface and delays coagulation within the fiber [ 35 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that, at 60% weight ratio, 1.55 mm bismuth embedded coating could attenuate 90% of X-ray photons at the 100 kV level, while the required thickness of a tungsten embedded coating was 1.73 mm for the same protection level. Qu et al fabricated a series of X-ray radiation-resistant fibres via a primarily industrialized wet-spinning trail, and knitted the resultant fibres into fabrics by knitting loom [9]. The X-ray attenuation ratio of the sample tended to increase with increasing barium sulphate content and finally reached a dose of a 0.1 mm thick lead equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…1 -I 0 initial intensity was counted without a fabric sample in air media. 2 -I intensity was counted while the sample is between detector and source Decay Scheme of Am-241[9]…”
mentioning
confidence: 99%